GC-MS ANALYSIS AND IN VITRO ANTIOXIDANT ACTIVITIES OF RUTA GRAVEOLENS L. FROM WESTERN GHATS REGION –SOUTH INDIA - KATHIRVEL POONKODI; Gomathi, Kalimuthu; Akila, Murugan; SUBRAMANIAN DEEPADEVI; ALAGUMALAI DHIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study examines the chemical composition of essential oil of Ruta graveolens and antioxidant activity of petroleum ether and methanol extracts of dry leaves of R. graveolens which belongs to Rutaceae family found in many parts of the India. There are few reports are available for its essential oil in India. Methods: The fresh leaves were hydrodistilled by Clevenger type apparatus, the obtained essential oil was analyzed using gas chromatography-mass spectrometry (GC-MS). The petroleum ether and methanol extracts were tested for antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) methods. Results: The GC-MS results showed that 2-nonanol (34.25), 2-nonanone (32.15) and nonyl ester (15.43) are the major components and some of the other minor compounds are 2-dodecanone (2.77), tridecanone (2.54) and tumeronol (2.16). The preliminary phytochemical investigation of petroleum ether and methanol extracts showed the presence of carbohydrates, phenolic compounds, flavonoids, furanocoumarins, fatty acids and alkaloids. Hence, an attempt was made to find the possible sources for future novel antioxidants in food and pharmaceutical formulations. Conclusions: GC-MS studies indicated that 2-nonanone (32.15) and nonyl ester (15.43) are the major components. The methanol extract showed highest inhibitory concentration values for DPPH (19.50±1.25 µg/ml) and ABTS (48.32±0.9 µg/ml) and petroleum ether extract showed moderate activity, both results are comparable with standard employed for each method.